Pengaruh Beban Pekerjaan terhadap Kinerja Karyawan: Efek Mediasi Burnout - Arie Fajriani; Dovi Septiari (Politeknik Negeri Batam, 2015)
The research purpouse is investigations burnout efffect as mediating variable on relationship between workload and employee performance. The sample is 709 employees in 163 manufacturing firms in Batam. Result show that burnout partially mediating the effect of workload on performance. Over workload will cause burnout on individual, than finally reduce performance.